2021
DOI: 10.1039/d0se01914c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of carbon deposition and its removal in solid oxide fuel cells by applying a non-conventional diagnostic tool

Abstract: Operating solid oxide fuel cells (SOFC) in a specific industry-relevant environment can result in undesired performance alterations and subsequent morphological changes. Conventional characterization tools, such as polarization curve or electrochemical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…For the purpose of this type of measurements, sinusoidal current or voltage amplitude is superimposed to the system running under d.c. (direct current) conditions. The height of the amplitude can vary between 4%-5% of the d.c. load value, fulfilling the main requirement of the linearity of the system under investigation [11][12][13][14][15][16][17]. The measured impedance spectra are correlated to either different processes that occur or specific electrodes, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purpose of this type of measurements, sinusoidal current or voltage amplitude is superimposed to the system running under d.c. (direct current) conditions. The height of the amplitude can vary between 4%-5% of the d.c. load value, fulfilling the main requirement of the linearity of the system under investigation [11][12][13][14][15][16][17]. The measured impedance spectra are correlated to either different processes that occur or specific electrodes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the main goal when applying this onlinemonitoring tool for real-system application is to not disturb the linear state, but to be able to identify non-linear mechanisms that occur in the system due to undesired failure modes. The pioneering results related to industrial-size cells with a surface of 80 cm 2 revealed very successful application of THD to identify the most relevant failure modes and degradation phenomena in SOFCs, namely (i) fuel starvation and thus implicitly Ni-reoxidation, (ii) air starvation and thus air electrode morphology changes, and (iii) carbon deposition [17,42,43]. The THD application was even helpful to identify carbon removal and SOFC performance regeneration [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fuel flexibility and efficiency demonstrated by SOFCs stem from their high operating temperature (600 -1000 °C), necessitated by the high activation barrier to oxide transport through the electrolyte (23). At these temperatures, the Ni based electrodes have excellent catalytic activity, although they are susceptible to a number of degradation pathways, particularly graphitic carbon formation (also referred to as coking) (7,21,(24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%